2023
DOI: 10.1021/jacs.3c04295
|View full text |Cite
|
Sign up to set email alerts
|

Pd(II) and Rh(I) Catalytic Precursors for Arene Alkenylation: Comparative Evaluation of Reactivity and Mechanism Based on Experimental and Computational Studies

Abstract: We combine experimental and computational investigations to compare and understand catalytic arene alkenylation using the Pd(II) and Rh(I) precursors Pd(OAc) 2 and [(η 2 -C 2 H 4 ) 2 Rh(μ-OAc)] 2 with arene, olefin, and Cu(II) carboxylate at elevated temperatures (>120 °C). Under specific conditions, previous computational and experimental efforts have identified heterotrimetallic cyclic PdCu 2 (η 2 -C 2 H 4 ) 3 (μ-OPiv) 6 and [(η 2 -C 2 H 4 ) 2 Rh(μ-OPiv) 2 ] 2 (μ-Cu) (OPiv = pivalate) species as likely activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 93 publications
1
16
0
Order By: Relevance
“…However, the lack of observed induction periods as well as the consistent change in linear/branched ratios seem to be most consistent with a homogeneous catalyst. Further, the proposed homogeneous mixed metallic Ir/Cu catalyst is consistent with our previous evidence for mixed metallic Rh/Cu and Pd/Cu catalysts for oxidative arene alkenylation. ,, …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, the lack of observed induction periods as well as the consistent change in linear/branched ratios seem to be most consistent with a homogeneous catalyst. Further, the proposed homogeneous mixed metallic Ir/Cu catalyst is consistent with our previous evidence for mixed metallic Rh/Cu and Pd/Cu catalysts for oxidative arene alkenylation. ,, …”
Section: Discussionsupporting
confidence: 90%
“…We propose that mixed metallic Rh/Cu and Pd/Cu species are likely active catalysts for styrene production (Scheme ). , Importantly, although our studies demonstrate that the structures shown in Scheme are likely the most active catalysts for the conversion of benzene, ethylene, and Cu­(II) carboxylate to styrene, we also propose that other mixed metallic species are viable catalysts . Thus, there is likely more than one active catalyst and the actual catalyst(s) can evolve with reaction conditions.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…15H 2 O/air as the oxidant in propionic acid, no reaction happening in acetic acid (Scheme 16b) [98] or Pd(OAc) 2 and Cu(OCOt-Bu) 2 through a reaction involving heterotrimetallic cyclic PdCu 2 (η 2 -C 2 H 4 ) 3 (μ-OPiv) 6 (Scheme 16c). [99] The aerobic Pd(OAc) 2 /heteropoly acid/EtCO 2 H procedure (Scheme 16b) has been used for oxida-tive coupling of arenes with α,β-unsaturated aldehydes [100a] and acrylonitriles. [100b] Jacobs and co-workers observed that the solvent-free Pd II -catalyzed reaction of anisole with 4phenylbut-3-en-2-one occurred faster in the presence of benzoic acid and without induction period, affording high yield of the DHR product (Scheme 17).…”
Section: Arene/alkene Couplingmentioning
confidence: 99%
“…In addition, deuterium-labeling experiments were carried out at low conversion to investigate kinetic isotope effects. An average kinetic isotope effect (k H /k D = 2.03) of three independent experiments suggested that Rh-mediated C–H activation might be the rate-determining step in this reaction (Scheme d, See SI for more details).…”
mentioning
confidence: 99%